Crosstalk Between ATP-P2X7 and Adenosine A2A Receptors Controlling Neuroinflammation in Rats Subject to Repeated Restraint Stress - Dias, Liliana; Lopes, Cátia R.; Gonçalves, Francisco Q.; Nunes, Ana; Pochmann, Daniela; Machado, Nuno J.; Tomé, Angelo R.; Agostinho, Paula; Cunha, Rodrigo A. (Frontiers in cellular neuroscience, 2021)
Depressive conditions precipitated by repeated stress are a major socio-economical burden in Western countries. Previous studies showed that ATP-P 2X7 receptors (P 2X7 R) and adenosine A 2A receptors (A 2A R) antagonists attenuate behavioral modifications upon exposure to repeated stress. Since it is unknown if these two purinergic modulation systems work independently, we now investigated a putative interplay between P 2X7 R and A 2A R. Adult rats exposed to restraint stress for 14 days displayed an anxious (thigmotaxis, elevated plus maze), depressive (anhedonia, increased immobility), and amnesic (modified Y maze, object displacement) profile, together with increased expression of Iba-1 (a marker of microglia “activation”) and interleukin-1β (IL1β) and tumor necrosis factor α (TNFα; proinflammatory cytokines) and an up-regulation of P 2X7 R (mRNA) and A 2A R (receptor binding) in the hippocampus and prefrontal cortex. All these features were attenuated by the P 2X7 R-preferring antagonist brilliant blue G (BBG, 45 mg/kg, i.p.) or by caffeine (0.3 g/L, p.o .), which affords neuroprotection through A 2A R blockade. Notably, BBG attenuated A 2A R upregulation and caffeine attenuated P 2X7 R upregulation. In microglial N9 cells, the P 2X7 R agonist BzATP (100 μM) or the A 2A R agonist CGS26180 (100 nM) increased calcium levels, which was abrogated by the P 2X7 R antagonist JNJ47965567 (1 μM) and by the A 2A R antagonist SCH58261 (50 nM), respectively; notably JNJ47965567 prevented the effect of CGS21680 and the effect of BzATP was attenuated by SCH58261 and increased by CGS21680. These results provide the first demonstration of a functional interaction between P 2X7 R and A 2A R controlling microglia reactivity likely involved in behavioral adaptive responses to stress and are illustrative of a cooperation between the two arms of the purinergic system in the control of brain function.